Self-centred leaders 'destroying' Umno - Daily Express, (KK) (Daily Express (KK), 2011)
KUALA LUMPUR: The transformation agenda of Prime Minister Datuk Seri Najib Tun Razak has continued to capture the imagination of members of the largest Malay party, Umno.